2022
DOI: 10.2147/idr.s397872
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of ESBL/AmpC-Producing Escherichia coli in Stray Dogs Sheltered in Yangzhou, China

Abstract: Limited data are available on the prevalence and antimicrobial resistance of extended spectrum β-lactamase-(ESBL) and AmpC β-lactamase-producing Escherichia coli in stray dogs. We aimed to investigate the genomic characteristics of ESBL/AmpCproducing E. coli isolated from stray dogs sheltered in Yangzhou, China. Methods: We collected 156 samples including 115 fecal swabs, 35 kennel floor swabs, two breeder hand and shoe sole swabs, and four feed samples. The isolates were tested for resistance by antimicrobial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
2
1
Order By: Relevance
“…The results of this study were compared with those of previous studies in China. We were surprised to find regional differences in the detection rate of ESBLs and the types of ESBL E. coli compared with previous studies [24,25]. However, a detailed phylogenetic comparison found that such geographical differences do not seem to be verified in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of this study were compared with those of previous studies in China. We were surprised to find regional differences in the detection rate of ESBLs and the types of ESBL E. coli compared with previous studies [24,25]. However, a detailed phylogenetic comparison found that such geographical differences do not seem to be verified in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…To examine the issue further, the results of this study were compared with those of previous studies in China. In the case of extended-spectrum β-lactamase (ESBL)-resistant E. coli, the rate of bla CTX−M in Yangzhou city was higher than the rates in the previous study (32). Furthermore, the differences were not only in rates but also gene types.…”
Section: Discussionmentioning
confidence: 80%
“…This E. coli sequence, type ST457, showed a remarkable ability to capture mobile elements that carry and transmit genes encoding resistance to clinically important antibiotics [35]. ST2325 is the most widespread in our study, and has so far been detected in a variety of environments, including livestock [38], stray dogs [39], food products (meat), and the environment (soil) [40]. It is primarily associated with ESBL-E. coli isolates.…”
Section: Genetic Diversity Of Ctx-resistant E Coli In Rabbit Farmsmentioning
confidence: 71%